Chest Drain Size: the Debate Continues - Hallifax, Robert J. (Curr Pulmonol Rep, 2017)
PURPOSE OF REVIEW: Small-bore chest tubes are widely used in the management of common pleural disease. Guidelines suggest that patients with malignant pleural effusions, pneumothorax and pleural infection may be successfully managed with small-bore drains. However, good quality data is often lacking. This article reviews the evidence for the treatment efficacy and potential adverse effects of different chest tube sizes. RECENT FINDINGS: In a large randomised study, the small difference in pain scores between large and small drains was not clinically significant. However, small-bore chest tubes commonly suffer from blockage or inadvertent removal, and may not be as effective in providing successful pleurodesis for malignant pleural effusions. SUMMARY: Although they may be effective in managing pleural infection, and less painful than large drains, small bore drains may be less effective for pleurodesis.